Teaching the Adjunct Experience - Binford, Arthur Leigh (Radical Teacher, 2017)
The article discusses an upper division capstone class in Sociology focused on the adjunct experience, premised on the idea that students and their families could be important allies in adjunct struggles if they knew more about the conditions and remuneration of this new faculty majority. Students carried out survey research with other students in order to ascertain their knowledge about adjuncts and interviews with adjunct volunteers. The article discusses the class and results.